2018
DOI: 10.4048/jbc.2018.21.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Treatment-Related Symptoms and Patient Outcomes in Breast Cancer: A Meta-Analysis

Abstract: PurposeAn association between endocrine treatment-related symptoms and breast cancer recurrence has been suggested previously; however, conflicting results have been reported. We performed a meta-analysis of published studies to clarify this relationship.MethodsWe systematically searched PubMed, Embase, Scopus, and the Cochrane database for studies investigating the association between endocrine treatment-related symptoms and patient survival. Random-effects meta-analysis was conducted with recurrence rate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Vaginal atrophy, vasomotor symptoms such as hot flashes [6][7][8] and musculoskeletal symptoms including joint pain and stiffness [9] are commonly reported adverse effects of adjuvant endocrine therapies with tamoxifen and/or AIs. Consistent with this, a recent metaanalysis showed that the occurrence of vasomotor and musculoskeletal symptoms is associated with a lower rate of breast cancer recurrence, an outcome associated with the administration of adjuvant endocrine therapies [10]. It therefore follows that the development of the above symptoms can be attributed to the active metabolites of the drugs used in adjuvant endocrine therapies (tamoxifen and AIs).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Vaginal atrophy, vasomotor symptoms such as hot flashes [6][7][8] and musculoskeletal symptoms including joint pain and stiffness [9] are commonly reported adverse effects of adjuvant endocrine therapies with tamoxifen and/or AIs. Consistent with this, a recent metaanalysis showed that the occurrence of vasomotor and musculoskeletal symptoms is associated with a lower rate of breast cancer recurrence, an outcome associated with the administration of adjuvant endocrine therapies [10]. It therefore follows that the development of the above symptoms can be attributed to the active metabolites of the drugs used in adjuvant endocrine therapies (tamoxifen and AIs).…”
Section: Introductionmentioning
confidence: 78%
“…In support of this finding, Lee et al [15] recently demonstrated that a dose reduction in tamoxifen treatment could reduce endoxifen levels and in turn result in patients' perceived alleviation of hot flashes. Moreover, as indicated above, a recent meta-analysis [10] also established the relationship between the occurrence of vasomotor or musculoskeletal symptoms and breast cancer recurrence, an outcome that may be influenced by CYP's metabolising activity [16][17][18], among patients who undergo endocrine therapy. Together, these findings suggest that CYP's activities may be linked to the occurrence and/or severity of these therapy-induced symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…While this association has not been consistently observed in all trials ( 49 , 69 ), there has been speculation regarding this observation. It has been suggested that patients reporting adverse effects are more adherent to therapy ( 70 ) or alternatively that patients with AIMSS are benefiting from greater reductions in estrogen levels with enhanced efficacy against HR+ breast cancer ( 71 ).…”
Section: Prevalence and Associated Risk Factorsmentioning
confidence: 99%
“…However, they may play an important indirect role in breast cancer prevention. Studies in the adjuvant setting have shown that endocrine therapy related side effects are associated with a reduction in breast cancer recurrence [ [25] , [26] , [27] , [28] , [29] ], which suggests that side effects might be a marker for predicting therapy benefit [ 30 ].…”
Section: Introductionmentioning
confidence: 99%